External validation of the 4C Mortality Score and PRIEST COVID-19 Clinical Severity Score in patients hospitalized with COVID-19 pneumonia in Greece - Paraskevas Themistoklis; Michailides Christos; Karalis Iosif; Kantanis Anastasios; Chourpiliadi Charikleia; Matthaiakaki Evgenia; Marangos Markos; Velissaris Dimitrios (Sciendo, 2022)
Background: Prognostic scores can be used to facilitate better management of patients suffering from life-threatening diseases, provided that they have been tested in the population of interest.